Peningkatan Daya Saing UMKM Bumbu Rujak Cak Mimin Untuk Menguasai Jangkauan Pasar Melalui Strategi Pemasaran - Amelia, Siska; Handayani, Wiwik (LPPM Politeknik Piksi Ganesha, 2024)
MSME Bumbu Rujak Cak Mimin faces challenges in increasing competitiveness and controlling a wider market reach. The preparation of marketing strategies is carried out to be able to excel in competition. The research was conducted with the aim of identifying an eﬀective marketing strategy in increasing the competitiveness of MSME Bumbu Rujak Cak Mimin. Through a qualitative approach, data is collected through interviews with business owners, observation and direct analysis of business activities. The results of the research show that the implementation of marketing strategies can signiﬁcantly increase the competitiveness and market reach of MSME Bumbu Rujak Cak Mimin. Thus, MSME Bumbu Rujak Cak Mimin can optimize market potential and strengthen its position in the traditional food industry through an integrated and innovative marketing strategy